2011
DOI: 10.1128/jvi.02514-10
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Homology-Directed Repair at I-SceI-Induced DNA Breaks during the Permissive Life Cycle of Human Cytomegalovirus

Abstract: Human cytomegalovirus (HCMV) selectively relocalizes many DNA repair proteins, thereby avoiding a potentially detrimental damage response. In the present study, we evaluated interactions between HCMV and the homology-directed repair (HDR) pathway. In permissive human foreskin fibroblasts, a fluorescence-based doublestranded break repair assay was used to determine that HCMV stimulated HDR. Repair of both stably integrated and extrachromosomal reporter substrates was observed to increase. HDR was also stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 52 publications
2
34
0
1
Order By: Relevance
“…These papers have examined the capacity of the cell's homologous recombination, base excision, nucleotide excision and non-homologous endjoining repair machinery to function, with the very large majority of the investigations finding decreased capacity of the cell to repair damage after viral protein expression (or full infection) commenced. Only four of these studies have reported evidence of an increase in repair capacity of the cell after infection or viral protein overexpression [21], [23], [36], [40]. Our results extend this analysis and separate the two genomes within an infected cell.…”
Section: Discussionsupporting
confidence: 80%
“…These papers have examined the capacity of the cell's homologous recombination, base excision, nucleotide excision and non-homologous endjoining repair machinery to function, with the very large majority of the investigations finding decreased capacity of the cell to repair damage after viral protein expression (or full infection) commenced. Only four of these studies have reported evidence of an increase in repair capacity of the cell after infection or viral protein overexpression [21], [23], [36], [40]. Our results extend this analysis and separate the two genomes within an infected cell.…”
Section: Discussionsupporting
confidence: 80%
“…Cells were trypsinized, washed, counted, and prepared as described previously (Kulkarni and Fortunato, 2011; Luo et al, 2007). Equivalent amounts of cell lysates (10 5 cell equivalents unless otherwise noted) were run on SDS-polyacrylamide gels, and then transferred to a Protran membrane (GE Healthcare Life Sciences).…”
Section: Methodsmentioning
confidence: 99%
“…The proposed model offers a mechanistic explanation for our previously reported results in wt HFFs [12]. The focus of the earlier HFF study was the recognition of viral manipulation of a cellular repair mechanism to its own ends in the context of a fully permissive infection.…”
Section: Resultsmentioning
confidence: 69%
“…( A ) Schematic diagram of reporter plasmid pDRGFP as described in [12]. ( B ) Representative IF staining of Ad-infected Clone 10.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation